Chemical control of banded leaf and sheath blight of maize - S.N. RAI, R.C. SHARMA and (Indian Phytopathology, 2002)
Rhizolex [tolelofoxmethyl] (at 10 g/10 litres) and thiophanate (at 7 g/10 litres) were effective in controlling Rhizoctonia solani f.sp. sasakii on maize varieties A 112 and A 123 in field and laboratory tests.